QUANTITATIVE METHOD OF ESTIMATE OF AERODROME BIRDS HAZARD RISK - V. A. Yudkin; M. A. Grabovski (Научный вестник МГТУ ГА, 2018)
The formalized parameters of bird hazard assessment at the aerodrome are presented. The size of total biomass of all birds that are in a zone of aircraft movement reflects the aggregate characteristic of ornithological hazard. This is a dynamic parameter, its dimensionality is kg/hour‧km2. The size of biomass is differentiated on high-altitude layers and the directions of its movement. In addition, it is necessary to estimate activity of each bird species at the aerodrome as component parts of bird hazard. Its dimensionality is individuals/hour‧km2. One more parameter of aerodrome bird hazard in the assessment process of activity of each bird species is the behavior pattern of birds in aerodrome airspace. This parameter will allow to reveal the sources of bird arrivals at the airfield and to detect the causes of it. Assessment of this share is necessary to choose the effective measures to decrease bird strike risk. The birds recording technique at airfield has been designed to obtain quantitative values of main parameters of bird hazard. The birds recording is carried out from the observation points located on the opposite sides of the runway. The birds recording technique is based on visual detection of birds, identification of species, sex and age determination, expert estimate of altitude and direction of their movement. Except the flying birds, the foraging and resting birds on the ground are also considered. The contribution of these birds to the aggregate value of ornithological hazard is bigger than overflying birds. The birds recording technique is described in detail. The norms and frequency of birds recording to obtain data on daily and seasonal dynamics of aerodrome bird hazard are substantiated. The algorithm of processing the results of birds recording and calculation of the main parameters value of bird hazard is stated. Gradations of bird hazard and relevant measures to decrease quantity of birds at airfield are proposed.